Are we exposing patients with a mildly elevated faecal calprotectin to unnecessary investigations?. Issue 3 (23rd July 2014) - Seenan, J P; Thomson, F; Rankin, K; Smith, K; Gaya, D R
Abstract : Objective: Faecal calprotectin (FC) is a non-invasive marker used to differentiate irritable bowel syndrome from inflammatory bowel disease (IBD). However, false positives are common. We sought to determine the diagnostic yield of investigation in patients presenting with new lower gastrointestinal (GI) symptoms and a mildly elevated FC (100–200 µg/g). Design: Retrospective study of electronic patient records. Patients: Patients aged 16–50 years with new lower GI symptoms and an FC 100–200 µg/g were identified from our biochemistry laboratory database between September 2009 and 2011. Patients were excluded if they had a previous FC >200 µg/g, were taking non-steroidal anti-inflammatory drugs (NSAIDs), had IBD, positive stool cultures or 'alarm' symptoms. Setting: Secondary care gastroenterology clinics. Results: 161 patients (103 female patients) were identified. Mean age was 37.3 years with a mean FC of 147 µg/g. 398 endoscopic, radiological and histological investigations were undertaken in 141 patients (an average of 2.8 investigations per patient). 131 colonoscopies were performed with abnormalities in only 24 (18.3%). In patients with a macroscopically normal upper GI endoscopy and colonoscopy, the diagnostic yield of any further investigation was only 7.3%. The negative predictive value (NPV) of an FC 100–200 µg/g was 86.7% for any pathology and 97.5% for significant luminal pathology (IBD, advanced adenoma or colorectal carcinoma). After a mean follow-up of 172.4 weeks, IBD was the final diagnosis in only 4 (2.5%) of patients. Conclusions: In adult patients under 50 years old presenting with new lower GI symptoms, the NPV of an FC between 100 and 200 µg/g in excluding significant organic GI disease is high.